A Correctness Checking Approach for Collaborative Business Processes in the Cloud. (11th February 2020) - Mo, Qi; Wang, Yuqi; Xiang, Jixiang; Li, Tong
Abstract : With the increasing popularity of cloud computing, especially the emergence of Business Process as a Service (BPaaS), more and more enterprises construct their process collaborations based on BPaaS services. Indeed, the collaborative business process built by BPaaS services can be seen as a complex system, as it covers multiple business processes (i.e., BPaaS services) and they act independently. Since business processes corresponding to BPaaS services are usually provided by different cloud service providers, and their interactions are unforeseen in advance, in actual execution, some behavioral anomalies (e.g., deadlocks) may occur. To this end, based on BPaaS services, we propose an approach to build process collaborations in the cloud. In this approach, we first model collaborative business processes using open nets. Then, we check their correctness based on stubborn sets. Finally, in case they are partially correct, we generate reliable paths for the coordination execution between business processes. Our approach is implemented in the PIPE (an open tool for Petri nets) and evaluated on actual cases that show its effectiveness and efficiency.